2003
DOI: 10.1291/hypres.26.s41
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Expression of Adrenomedullin during Adipocyte-Differentiation of 3T3-L1 Cells

Abstract: Adrenomedullin (AM) is a potent vasodilator peptide which has an inhibitory action on insulin secretion.Resistin is a novel peptide specifically secreted from adipocytes, and implicated in insulin resistance. We

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
1

Year Published

2004
2004
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 30 publications
0
5
1
Order By: Relevance
“…It has been recently reported that AM mRNA expression in 3T3-L1 cells decreased during preadipocyte differentiation by day 4 (19,20). In contrast, our present study employing longer incubation periods (3-9 days) clearly demonstrated that AM mRNA expression as well as IR-AM secretion decreased to a very low level during the early predifferentiation phase (day 3) but markedly increased during the late phase (days 6 -9).…”
Section: Discussioncontrasting
confidence: 69%
“…It has been recently reported that AM mRNA expression in 3T3-L1 cells decreased during preadipocyte differentiation by day 4 (19,20). In contrast, our present study employing longer incubation periods (3-9 days) clearly demonstrated that AM mRNA expression as well as IR-AM secretion decreased to a very low level during the early predifferentiation phase (day 3) but markedly increased during the late phase (days 6 -9).…”
Section: Discussioncontrasting
confidence: 69%
“…However, reported studies of the expression of AM in preadipocytes during differentiation and in adipocytes are limited and inconsistent. Li et al (14) studied the expression of AM and resistin in 3T3-L1 preadipocytes and adipocytes by Northern blot analysis and showed that AM mRNA was expressed in 3T3-L1 preadipocytes but was undetectable in adipocytes, whereas resistin mRNA was not detected in 3T3-L1 preadipocytes but was expressed in adipocytes. It was also reported that preadipocytes at early differentiation stages secreted AM, but mature adipocytes did not secrete AM (34).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies demonstrated that rat adipose tissue contains AM mRNA (14,23), and adipose tissue obtained from rats fed a high-fat diet expresses greater amounts of AM than that obtained from rats fed a normal diet (2). In addition, studies in humans showed that plasma AM correlates with body mass index, and circulating AM is elevated in overweight patients with essential hypertension (34) and is decreased with a reduction of body weight by a hypocaloric diet (18), suggesting a role of AM in human adipose tissue.…”
mentioning
confidence: 99%
“…However, we (41) previously demonstrated that the kinetics of AM secretion from sWAT preadipocytes undergoing in vitro differentiation was opposite to that of leptin. Also, Li et al (28) showed that AM mRNA was expressed in 3T3-L1 preadipocytes but was undetectable in adipocytes and that AM immunoreactivity was detected in the culture media of 3T3-L1 preadipocytes and adipocytes, with higher concentrations found in preadipocytes. Taken together, the above-mentioned observations suggest that preadipocytes in eWAT can synthesize AM.…”
Section: Discussionmentioning
confidence: 99%